Ten-years comparative study after surgical treatment of perforated peptic ulcer according to ulcer relapse between H. Pylori positive, after eradication, and negative patients Estudo comparativo quanto à recidiva ulcerosa do tratamento cirúrgico de úlcera péptica perfurada entre pacientes H. Pylori positivos, após erradicação, e negativos - Rosa Pachaly Dalcin; Cristiano Antoniazzi Abaid; Paola M. Almeida; Samia B. Adaime; Thiza Massaia Londero; Lucas V. Gai (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2009)
BACKGROUND: The surgical treatment for perforated peptic ulcer is still a matter of discussion. The surgeons, for many years, made their options between acid-reducing procedures with some morbi-mortality and simpler procedures like closure of the perforation. But, in these cases, were faced with a high chance of ulcer relapse. Since the proved link between peptic ulcer and gastroduodenal infection caused by H. pylori, a recommendation for a change in their attitudes going back to simpler procedures with eradication of the bacteria was done. AIM: To analyse ulcer recurrence in patients treated with the same surgical procedure but belonging to two different groups: positive and negative to H. pilori. METHODS: A total of 144 patients were treated with simple closure of their perforated pre-pyloric, pyloric and duodenal ulcers. Thirty days after operation they were submitted to upper endoscopy and tested for the bacteria by urease and histopathological exams and divided into two groups according to the results of the tests: positive and negative. The positive ones were eradicated and, together with the negative group, were followed through six months interval endoscopies and detection tests looking for ulcer relapses and reinfection in the eradicated group. The positive group consisted of 25 patients, with two patients considered non eradicable according to the treatment protocol. They were followed for an average period of 38,21 months. RESULTS: Relapse was detected in four patients (17,39%), half of them (8,69%) were reinfected. The negative group consisted of 26 patients, with a median follow-up of 38,28 months and eight (30,76%) relapses were detected. There was no statistical significant difference due probably to the high dropout of patients. CONCLUSION: Simple suture with H. pilori eradication is the gold standard for the positive group, leaving the question of acid-reducing procedures open for the negative ones. RACIONAL: O tratamento cirúrgico da úlcera péptica perfurada é assunto discutível. Os cirurgiões, por muitos anos, fizeram suas opções entre procedimentos de redução ácida, somente fechamento da perfuração - porém com maior chance de recidiva ulcerosa. Desde a comprovada vinculação da úlcera péptica e suas complicações à infecção gastroduodenal causada pelo Helicobacter pylori, houve recomendação para mudança na atitude dos cirurgiões na volta à operação mais simples com erradicação da bactéria. OBJETIVO: Analisar a recidiva ulcerosa em pacientes com úlcera perfurada H. pylori positiva que foram submetidos à simples sutura da lesão e omentopexia com erradicação da bactéria e compará-la com H. pylori negativo submetido ao mesmo tratamento cirúrgico. MÉTODOS: Cento e quatorze pacientes com úlceras pré-pilóricas, pilóricas e duodenais perfuradas foram atendidos com fechamento simples. Trinta dias após a operação submeteram-se à endoscopia digestiva alta com biópsias para testes da urease e histopatológicos. Foram divididos em dois grupos de acordo com o resultado dos testes: positivo e negativo.Os positivos foram erradicados e, junto com o grupo negativo, foram seguidos com endoscopias semestrais e testes de detecção para H. pylori procurando por recidiva ulcerosa e reinfecção no grupo erradicado. RESULTADOS: O grupo positivo foi formado por 25 pacientes, dos quais dois foram considerados não erradicáveis segundo os critérios do protocolo. Os demais foram seguidos por período médio de 38,21 meses e detectadas recidivas em quatro pacientes (17,39%), metade deles (8,69%) foram reinfectados. O grupo negativo foi formado por 26 pacientes, seguido por período médio de 38,28 meses e oito (30,76%) apresentaram recidiva ulcerosa. Não foi evidenciada diferença estatisticamente significativa entre os grupos. CONCLUSÃO: Em relação à recidiva ulcerosa, o fechamento simples seguido de erradicação da bactéria é o procedimento padrão para o grupo positivo; deixa-se em aberto a questão dos procedimentos ácido-redutores para o grupo negativo.